Continuous Flow Multigram-Scale Synthesis of Cetylpyridinium Chloride - Patel, Kashyap; Kapdi, Anant R.; Shinde, Manish Manohar; Veeramani, Karuna; Oruganti, Srinivas (Sustainability & Circularity NOW, 2024)
Cetylpyridinium chloride is popularly employed as an antimicrobial agent in high-volume commodity and consumer products. Given its high tonnage requirements annually, challenges in its synthesis using conventional batch manufacturing involving higher reaction temperatures at scale, lower yields and purity, and excessively long reaction times could be circumvented by adopting continuous flow as a safe and sustainable approach. We herein report a facile, gram-scale continuous flow protocol for the synthesis of cetylpyridinium chloride (CPC) that reduces reaction time from ≥24 hours to 30 minutes with an isolated product yield of >90% and an HPLC purity of >99%.
Keywords: Antimicrobial; Cetylpyridinium chloride; Continuous flow; High-T